Determinants of Female Entrepreneurship Success in the Agricultural Sector: An Examination of SMEs in South Africa - Kanayo, Ogujiuba (International Journal of Economics and Financial Issues, 2021)
The Agricultural sector in South Africa is amongst the main contributors to job-creation South Africa. Since the post-apartheid era, South Africa has seen a severe transformation in this sector, of which previously disadvantaged farmers (especially women) are now on the forefront in terms of new developments, and SME business expansion. However, the efforts of the government to sustain SMEs are yet to alleviate the challenges agricultural SMEs are facing. This article looks at the determinants of business successes for female owned SMEs. The trustworthiness and internal consistency examination of the instrument was done, with test re-test reliability method and Cronbach Alpha index. They both generated an R-value of 0.70 and 0.875 respectively. Multiple Regression technique was used in estimating the coefficients' of impact on success. Findings showed that certain characteristics of the entrepreneur, including Entrepreneurship Skill, Financial Resources, Capital Start-up Amount and Customer and Market Access have a significant impact on Female Entrepreneurship Success. We recommend a major overhaul of government interventions designed to enhance the skills of female entrepreneurs as well as broadening their customer and market access base. This has become imperative for addressing the challenges of business success for female entrepreneurs. Keywords: Business, Entrepreneurship, Female, SME JEL Classifications: D6, M1, M2 DOI: https://doi.org/10.32479/ijefi.11274